Adapting an acyl CoA ligase from Metallosphaera sedula for lactam formation by structure-guided protein engineering - Capra, Nikolas; Lelièvre, Chloé; Touré, Océane; Fossey-Jouenne, Aurélie; Vergne-Vaxelaire, Carine; Janssen, Dick B.; Thunnissen, Andy-Mark W. H.; Zaparucha, Anne (Frontiers in Catalysis, 2024)
The CoA ligase from Metallosphaera sedula (MsACL) can be used for the chemoenzymatic synthesis of amides from carboxylic acids. In this CoA-independent conversion, the enzyme catalyzes the adenylation of a carboxylic acid with the help of ATP, followed by the uncatalyzed cleavage of acyl-AMP by a nucleophilic amine to yield an amide. With ω -amino acids as substrates this reaction may result in formation of lactams, but unfortunately the substrate preference of the wild-type enzyme is rather limited. To allow structure-based protein engineering and expand the substrate scope of the enzyme, crystal structures of MsACL were solved in the thioesterification conformational state with AMP, CoA and with the reaction intermediate acetyl-AMP bound in the active site. Using substrate docking and by comparing the crystals structures and sequence of MsACL to those of related CoA ligases, mutations were predicted which increase the affinity in the carboxylic acid binding pocket for ω-amino acids. The resulting mutations transformed a non-active enzyme into an active enzyme for -caprolactam synthesis, highlighting the potential of the thermophilic CoA ligase for this synthetic and biotechnologically relevant reaction.